SUSTAINING PEACE AND JUSTICE: HOW ABOUT PUBLIC'S PERSPECTIVE ON POLICE - Shahriza Ilyana Binti Ramli; Nurul Syazana Binti Elias; Nor Najihah Binti Abdul Halim (Journal of Islamic, Social, Economics and Development, 2023)
Public in general is known as adult. The World Health Organization defines an adult as someone is older than 19 years old, subject to national law. Adults have responsibilities and duties that children, teenagers, and the majority of people in their twenties do not, which give life meaning and purpose. The public in general should be secured of peace and justice in doing daily activities. Obviously, the police have a significant role in achieving this goal. This paper will discuss the public's perspective on police. Among the influencing factors are social media, corruption and integrity. It is also closely related to the 16th Sustainable Development Goals (SDG) which promotes inclusive and peaceful societies, ensuring that everyone has access to justice, and creating inclusive institutions at all levels. No matter their ethnicity, religious or beliefs, everyone should be safe from all types of violence and feel secure as they go about their daily lives.